ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) REPORTING: ENHANCING TRANSPARENCY IN SUSTAINABLE FINANCE - Getah Ester Hayatullah; Napat Chai; Ming Pong (Yayasan Adra Karima Hubbi, 2026)
The growing emphasis on sustainability within global financial markets has elevated Environmental, Social, and Governance (ESG) reporting as a central mechanism for enhancing transparency and accountability in sustainable finance. Investors, regulators, and other stakeholders increasingly rely on ESG disclosures to evaluate non-financial risks, long-term value creation, and corporate responsibility. This study aims to analyze the role of ESG reporting in improving transparency and its implications for sustainable finance practices. The research adopts a qualitative analytical approach based on a systematic review of peer-reviewed academic literature, international reporting standards, regulatory frameworks, and secondary data from sustainability reports and financial institutions. The findings indicate that high-quality ESG reporting enhances information transparency, reduces information asymmetry, and strengthens investor confidence by enabling more accurate assessment of corporate sustainability performance. Consistent and standardized ESG disclosures are associated with improved capital allocation efficiency, lower perceived risk, and stronger stakeholder trust. The study concludes that ESG reporting is a critical instrument for advancing sustainable finance, provided it is supported by harmonized standards, robust governance mechanisms, and credible verification processes.